SOFSEM 2017 : theory and practice of computer science : 43rd International Conference on Current Trends in Theory and Practice of Computer Science, Limerick, Ireland, January 16-20, 2017, proceedings /: theory and practice of computer science : 43rd International Conference on Current Trends in Theory and Practice of Computer Science, Limerick, Ireland, January 16-20, 2017, proceedings. (2017) - Unknown
No abstract available